SOSIALISASI PEMBUATAN BIOGAS BAHAN BAKU TINJA PUYUH - Sudarman, Sudarman; Basyrun, Basyrun (Universitas Negeri Semarang, 2017)
This activity aims to provide training on making biogas with raw materials of quail stool. Community service activities are conducted in the District Mranggen Demak District. Based on the results of this activity there is an increase of knowledge and skill to make biogas installation